2016
DOI: 10.1177/1049731516666382
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Child-Custody Recommendations of Israeli Arab Social Workers

Abstract: Objectives: To evaluate Israeli Arab social workers' custody recommendations, given the unique cultural context in which they operate. Methods: The current study used an experimental-design embedded within a survey. Data regarding custody recommendations were collected from 137 Israeli Arab social workers. Results: Israeli Arab social workers tend to adhere to traditional norms and prefer mother's custody (odds ratio [OR] ¼ 3.74; effect size [ES] ¼ 0.73) over father's (OR ¼ 0.05; ES ¼ À1.65) and joint custody … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
1
6
1
Order By: Relevance
“…Hence, it emerges that social workers who defined themselves as religious, conservative, and/or collectivistic recommended out-of-home placements for children at high risk, despite the contradiction with accepted cultural perceptions in Arab society. This contrasts findings of a previous study on custodial arrangements in divorce in which cultural perceptions were found to influence the social worker's decision (Enosh et al, 2016). Although in both cases, the social worker's decision involves interpretations and perceptions based on cultural values including commitment to preserving children's relationships with their families, communities, and culture, in high-risk cases, there seems to be a cross-cultural consensus regarding the need to exercise only professional considerations to protect and prevent harm to children.…”
Section: Discussion and Applications To Practicecontrasting
confidence: 99%
See 3 more Smart Citations
“…Hence, it emerges that social workers who defined themselves as religious, conservative, and/or collectivistic recommended out-of-home placements for children at high risk, despite the contradiction with accepted cultural perceptions in Arab society. This contrasts findings of a previous study on custodial arrangements in divorce in which cultural perceptions were found to influence the social worker's decision (Enosh et al, 2016). Although in both cases, the social worker's decision involves interpretations and perceptions based on cultural values including commitment to preserving children's relationships with their families, communities, and culture, in high-risk cases, there seems to be a cross-cultural consensus regarding the need to exercise only professional considerations to protect and prevent harm to children.…”
Section: Discussion and Applications To Practicecontrasting
confidence: 99%
“…In terms of education, 75.5% were at the BA in social work level, 24.5% had achieved an MA in social work degree or were studying toward it. This distribution of personal and professional characteristics is similar to the distribution of personal and professional characteristics of social workers in other similar surveys, regardless of religious affinity or ethnicity (e.g., Enosh, Nouman, & Anabtawi, 2016;Nouman et al, 2016). In terms of religious affiliation, 68% were Muslims, 26% were Christians, and 6% were Druze; 77% defined themselves as religious or traditional and 57% defined themselves as conservative (rather than liberal).…”
Section: Sample and Sampling Proceduressupporting
confidence: 79%
See 2 more Smart Citations
“…However, in cases of great ambiguity regarding the facts or applicable criteria, the social worker will be inclined to use heuristic (intuitive) methods to reach a decision. As a result, decisions in cases of great uncertainty might be sensitive to heuristics and personal biases such as cultural and professional differences or organizational culture and might lead to bias in professional considerations (e.g., Enosh & Bayer-Topilsky, 2014;Enosh, Nouman, & Anabtawi, 2016;Nouman, Enosh, & Niselbaum-Atzur, 2016).…”
Section: The Dual Process Of Judgmentmentioning
confidence: 99%